2004
DOI: 10.1038/sj.leu.2403423
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation normalizes abnormal bone remodeling and sRANKL/osteoprotegerin ratio in patients with multiple myeloma

Abstract: The osteoprotegerin (OPG)/receptor activator of NF-kappa B ligand (RANKL) system has a major role in the pathogenesis of bone disease in myeloma (MM). The effect of autologous stem cell transplantation (ASCT) on bone turnover in MM was evaluated in 51 patients (35M/16F). Markers of bone resorption (NTX, TRACP-5b), bone formation (bone-alkaline phosphatase (bALP), osteocalcin), OPG and sRANKL were measured preand every month post-ASCT. The median follow-up period was 12 months. Four patients were transplanted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 32 publications
2
40
2
Order By: Relevance
“…83 The RANKL/OPG ratio has been found to correlate with OS in MM. This result has not been confirmed in all reported studies to date, 63,69,83,84 may be due to differences in patient populations and/or therapies administered. Further studies are needed before measurement of serum RANKL and OPG levels in the everyday clinical setting should be considered.…”
Section: Correlations Of Bone Turnover Markers With Myeloma Activity contrasting
confidence: 48%
See 3 more Smart Citations
“…83 The RANKL/OPG ratio has been found to correlate with OS in MM. This result has not been confirmed in all reported studies to date, 63,69,83,84 may be due to differences in patient populations and/or therapies administered. Further studies are needed before measurement of serum RANKL and OPG levels in the everyday clinical setting should be considered.…”
Section: Correlations Of Bone Turnover Markers With Myeloma Activity contrasting
confidence: 48%
“…46,48,[51][52][53][54][55][56][58][59][60] Urinary NTX levels were increased even in myeloma patients who had reached a clinical plateau phase of their disease, 61 whereas PYD, DPD and NTX were also elevated in myeloma patients before autologous transplantation. 62,63 A histomorphometric study in bone marrow biopsies of myeloma patients showed that urinary NTX correlated most positively with dynamic histomorphometric indices of bone resorption, followed by serum ICTP and urine DPD; urine PYD did not correlate with the histomorphometric findings. 64 Moreover, comparison between these four markers (PYD, DPD, NTX and ICTP) revealed that serum ICTP and urinary NTX better reflected the extent of myeloma bone disease and could better predict early progression of the bone disease after conventional chemotherapy (CC).…”
Section: Markers Of Bone Remodeling In Myeloma Bone Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…However, markers of bone formation do not return to normal until the 8 month postASCT, providing an indication that bone formation may be delayed in normalizing. 15 It has been suggested that the failure of serum markers of bone formation to increase in the period after increased bone resorption is due to the selective impairment of the osteoblastic compartment after HDT. 16,17 Our results could indicate that osteoblasts may resume their function when the inhibitory effect of DKK-1 is no longer present.…”
Section: Dkk-1 and Asctmentioning
confidence: 99%